105k views
16 votes
Step by Step: Solve:
3x + 2 ( 2x + 9 ) = 4

2 Answers

2 votes
3x+2 (2x+9) = 4

Take care of the parenthesis to get the following

3x + 4x + 18 = 4

Add the X values

7x + 18 = 4

Take 18 from both sides so it looks like this

7x = 4 - 18

From this you’ll get this

7x = -14

Divide both sides by 7

x = -14 / 7

Simplify

X = 7 * - 2 / 7

Simplify

X = -2
User Piotr Tomasik
by
5.7k points
5 votes

Answer:

3x + 2 (2x + 9) = 4

3x + 4x + 18 = 4

7x + 18 = 4

7x = -14

x = -2

Explanation:

i think it should be -2. if im wrong sorry

User Sufian Saory
by
4.9k points